2017
DOI: 10.1097/j.pain.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

Opioid prescription levels and postoperative outcomes in orthopedic surgery

Abstract: Given the basic need for opioids in the perioperative setting, we investigated associations between opioid prescription levels and postoperative outcomes using population-based data of orthopedic surgery patients. We hypothesized that increased opioid amounts would be associated with higher risk for postoperative complications. Data were extracted from the national Premier Perspective database (2006-2013); N = 1,035,578 lower joint arthroplasties and N = 220,953 spine fusions. Multilevel multivariable logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
110
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 39 publications
3
110
1
3
Order By: Relevance
“…This descriptive multicenter study on analgesic consumption trajectories during the first year following THA and TKA in an unselected patient population, found that although the majority of patients had reduced analgesic consumption, a clinically significant proportion of patients had unchanged or increased use of analgesics 9–12 months after surgery. Thus, despite a fast‐track set‐up including the use of opioid‐sparing analgesia, our findings support previous reports of increased or continued analgesic use in a considerable proportion of THA and TKA patients (Fuzier et al., ; Pivec et al., ; Inacio et al., ; Cozowicz et al., ; Hansen et al., 2017), although the higher incidence of preoperative opioid use in the Danish population (Birke et al., ) could potentially increase postoperative opioid use.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This descriptive multicenter study on analgesic consumption trajectories during the first year following THA and TKA in an unselected patient population, found that although the majority of patients had reduced analgesic consumption, a clinically significant proportion of patients had unchanged or increased use of analgesics 9–12 months after surgery. Thus, despite a fast‐track set‐up including the use of opioid‐sparing analgesia, our findings support previous reports of increased or continued analgesic use in a considerable proportion of THA and TKA patients (Fuzier et al., ; Pivec et al., ; Inacio et al., ; Cozowicz et al., ; Hansen et al., 2017), although the higher incidence of preoperative opioid use in the Danish population (Birke et al., ) could potentially increase postoperative opioid use.…”
Section: Discussionsupporting
confidence: 88%
“…Although total hip and knee arthroplasty (THA/TKA) are performed to relieve pain and regain function, treatment failure resulting in persistent pain occurs in 10–20% of patients (Braden et al., ; Beswick et al., ; Lewis et al., ; Lenguerrand et al., ). This may subsequently lead to increased consumption of opioids and other analgesics, with associated risk of adverse effects (Cozowicz et al., ) including endocrine dysfunction (Bawor et al., ), cognitive impairment (Katz and Mazer, ), addiction (Kharasch and Brunt, ), tolerance (Birke et al., ) and a general increased risk of morbidity (Lanas and Sopena, ; Kuo et al., ; Bawor et al., ; Ravel et al., ) and mortality (Ekholm et al., ; Birke et al., ; Rudd et al., ; Sondergaard et al., ). Despite the well‐documented risk for persistent pain (Wylde et al., ; Lewis et al., ; Lenguerrand et al., ) and associated risk of analgesic use, only a limited number of large‐scale studies have investigated opioid consumption after primary THA (Blagestad et al., ; Inacio et al., ; Namba et al., ) or TKA (Fuzier et al., ; Goesling et al., ; Bedard et al., ; Hansen et al., ), and few have included data on non‐opioid analgesic use (Fuzier et al., ; Blagestad et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These complications can be particularly detrimental in patients who have undergone thoracic surgery, as these patients have reduced lung function due to chronic obstructive pulmonary disease and lung cancer. Other potential complications related to high dose opioids include an increased risk of deep vein thrombosis, gastrointestinal, infectious, and urinary complications [19]. Furthermore, studies have shown that high dose opioids can increase the risk of recurrence of certain types of cancer which has been attributed to the immunosuppressive effects of opioids [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective outcome data from more than one million joint arthroplasties and 200,000 spinal surgeries in the US showed that even after adjusting for preoperative chronic pain and substance use the highest quartile opioid dose compared with the lowest quartile in the first 48 hours postoperatively was associated with a 50% increase in deep vein thrombosis and infective complications, with significant increases in urinary, gastrointestinal complications as well as length of stay. 13 As a significant driver of increased postoperative opioid use without measurable benefit, measures of use of slow-release opioids in acute pain should be included as a measure for local opioid stewardship programs in future.…”
mentioning
confidence: 99%